(untitled) (Journal of Chitwan Medical College, 2020)
Background: Medical students are normally under extreme pressure due to the vast syllabus they have to cover within few years of their student life. The stress due to academic pressure and sudden change in lifestyle tend to affect their sleeping habits, which is considered as one of the potential risk factors for obesity. This study aimed to observe the association between sleep duration, sleep quality and body mass index in medical students. Methods: This is a cross-section study conducted among 269 medical students. Self-reported sleep duration was noted, sleep quality was assessed with Pittsburgh Sleep Quality Index (PSQI) questionnaire. Height in cm and weight in kg was recorded and BMI was calculated. The data obtained was divided into different groups according to sleep duration, sleep quality and BMI. ANOVA and independent t-test was done using Statistical Package for the Social Sciences version 25 for statistical analysis. p< 0.05 was considered statistically significant. Results: In general, 24 (8.9%) of students were underweight, 187 (69.5%) had normal weight, 51 (19%) were overweight and 7 (2.6%) were obese. 94 (34.9%) students reported to spent <7 hours in bed and 98 (36.4%) students had poor sleep quality. Mean BMI was significantly higher in students with short sleep (p-value=0.001, ANOVA) and in students with poor sleep quality (p-value=0.000, independent t-test). Conclusions: Higher BMI was observed in the group of students having poor sleep quality and short sleep duration. Furthermore, poor sleep quality was more prominent in women than in men.